2009
DOI: 10.1177/0741088309351547
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Features of Writing Quality

Abstract: In this study, a corpus of expert-graded essays, based on a standardized scoring rubric, is computationally evaluated so as to distinguish the differences between those essays that were rated as high and those rated as low. The automated tool, Coh-Metrix, is used to examine the degree to which high- and low-proficiency essays can be predicted by linguistic indices of cohesion (i.e., coreference and connectives), syntactic complexity (e.g., number of words before the main verb, sentence structure overlap), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
320
4
34

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(382 citation statements)
references
References 40 publications
24
320
4
34
Order By: Relevance
“…Various studies have shown MTLD to be at least as effective as the industry standard vocd-D index, and even one of the most informative and distinguishing variables in the entire arsenal of several hundred Coh-Metrix indices (see Crossley, Salsbury, & McNamara, 2009;McNamara et al, 2010). Such successes do not mean that all the settings of the MTLD approach are optimal.…”
Section: Preliminary Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…Various studies have shown MTLD to be at least as effective as the industry standard vocd-D index, and even one of the most informative and distinguishing variables in the entire arsenal of several hundred Coh-Metrix indices (see Crossley, Salsbury, & McNamara, 2009;McNamara et al, 2010). Such successes do not mean that all the settings of the MTLD approach are optimal.…”
Section: Preliminary Analysesmentioning
confidence: 97%
“…This default factor size is used in the MTLD prototype that features in the Coh-Metrix suite of textual analysis indices and is the factor size used in the engineering studies that have incorporated MTLD (e.g., Crossley & McNamara, in press;McNamara et al, 2010).…”
Section: Factor Sizementioning
confidence: 99%
“…Hence, it is also relevant and important to investigate these aspects in teachers' writing as an indication of their writing proficiency and quality. While there have been studies done on students' cohesion and use of cohesive devices in writing (Crossley & McNamara, 2010a;McNamara, Crossley, & McCarthy, 2010;Tangkiengsirisin, 2010), little research has been done on cohesive errors (Sadighi & Heydari, 2012). However, Sadighi and Heydari's (2012) study did find that students of differing levels of proficiency made more errors in different types of cohesion devices.…”
Section: Often Still Esl Learners Themselves?mentioning
confidence: 99%
“…They test three Coh-Metrix indices that had been found sufficient to predict human-scored writing quality of average-performing college students (McNamara et al 2010). While these indices are not good predictors for the low-performing adults, ten other Coh-Metrix indices were identified that were predictive for this population.…”
Section: Automated Rubrics and Support For Source-based Writingmentioning
confidence: 99%